Acute effects of a neuromuscular warm-up on potential re-injury risk factors associated with unanticipated jump landings after anterior cruciate ligament reconstruction: A crossover trial. (November 2021) - Ashigbi, Evans Y.K.; Giesche, Florian; Groneberg, David A.; Banzer, Winfried; Niederer, Daniel
Abstract: Objective: To investigate acute effects of a single bout of football specific neuromuscular injury preventive warm-up on potential anterior cruciate ligament (ACL) re-injury risk factors during anticipated and unanticipated jump-landings. Design: Crossover. Methods: Fourteen participants (mean ± SD age, 23.4 ± 4.1 years) 6–24 months after ACL reconstruction performed the Prevent Injury and Enhance Performance (PEP) and bicycle ergometer warm-up in a randomised sequence. Washout phase was one week. Countermovement jumps with anticipated and unanticipated single-leg-landings were assessed. Decision-making quality was measured using landing error count. Results: No carry-over effects occurred (p > 0.05). The unanticipated task produced significantly higher peak ground reaction forces (Δ+4%, F(11) = 3.46, p < 0.001, eta 2 = 0.21) after PEP warm-up compared to ergometer warm-up. A lower number of decision (Δ+12%, F (5) = 17.1, p < 0.001, eta 2 = 0.57) and cumulated (Δ+15%, F (3) = 17.2, p < 0.001, eta 2 = 0.57) errors were recorded during the unanticipated condition following PEP compared to ergometer warm-up. Conclusions: Evaluating unanticipated jump-landing ability prior to return to sports clearance may provide information on potential re-injury risk factors. PEP warm-up may be superior to bicycle ergometer warm-up at improving unanticipated decision-making quality among athletes cleared to return to sports. Highlights: Higher peak ground reaction force values were produced after the PEP warm-up. Decision-making quality generally improved following both warm-ups. Unaticipated decision making was more enhanced after the PEP warm-up. Unanticipated jump-landing assessment may provide re-injury risk information.